Judaism and the interpretation of scripture: introduction to the rabbinic midrash - Neusner, Jacob (Hendrickson, 2004)
How does Judaism read scripture? -- An overview of the rabbinic midrash-compilations -- Genesis in Genesis Rabbah : recasting the patriarchs into the models for Israelite conduct -- Exodus in Mekhilta attributed to R. Ishmael : reorganizing the facts of scripture into coherent expositions on important topics -- Leviticus in Sifra : mediating between the two Torahs, oral and written -- Leviticus in Leviticus Rabbah : turning scripture's laws into the design of holy Israel's social order -- Numbers in Sifré to Numbers : systematically reading and expounding scripture's narratives in accord with the rabbinic model -- Deuteronomy in Sifré to Deuteronomy : turning scripture's cases into laws, and laws into an entire social system -- Esther in Esther Rabbah I : a woman saves Israel -- Ruth in Ruth Rabbah : a gentile woman saves Israel through the Torah -- Song of Songs in Song of Songs Rabbah : reading holy Israel's relationship to God within the symbols of a love-song -- Lamentations in Lamentations Rabbah : updating scripture's response to the First Temple's destruction by showing how an event defines a pattern -- The calendar of Judaism in Pesiqta deRab Kahana : telling time by Judaism's clock -- The sages in the Fathers according to Rabbi Nathan -- The theology of rabbinic midrash